Characterization of carbapenem-resistant Klebsiella pneumoniae from blood cultures in Gaza Strip hospitals, Palestine - Nahed Al Laham; Ahmed Al Afifi; Alexander Mellmann; Frieder Schaumburg (International Journal of Medical Microbiology)
Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a difficult to treat organism owing to limited therapeutic options. So far, little is known about the molecular characteristics of CRKP in Palestine. Objectives: The aim of this study was to investigate the antimicrobial resistance patterns, multilocus sequence types (ST) and resistance genes among clinical K. pneumoniae isolates from hospitalized patients in Gaza Strip, Palestine. Methods: K. pneumoniae from blood cultures (n = 55) were collected at two hospitals in Gaza Strip (2023) and identified by MALDI-TOF-MS. Antimicrobial susceptibility testing was done using VITEK-2 automated systems. Carbapenemases were phenotypically detected. Whole genome sequencing (WGS) of all CRKP isolates was performed to assess determinants for carbapenem resistance and genotypes. Results: Of all K. pneumoniae isolates, 40 % (n = 22/55) were CRKP. Among CRKP, cefiderocol showed the least resistance (46 %, n = 10/22) while ceftazidime/avibactam showed a synergistic effect with aztreonam (36 %, n = 8/22). The majority (86 %, n = 19/22) of CRKP carried metallo-β-lactamases, and only 9 % (n = 2/22) encoded OXA-48 carbapenemase. WGS of CRKP revealed that the predominant genotype is multilocus sequence type ST147 harboring blaNDM-5 and blaCTX-M-15. Conclusion: The proportion of CRKP among all K. pneumoniae from bloodstream infection in Gaza Strip is high (40 %) and mainly associated with the blaNDM-5-positive high-risk clone ST147.